2020
DOI: 10.1136/neurintsurg-2020-016597
|View full text |Cite
|
Sign up to set email alerts
|

The 'armed concrete' approach: stent-screw-assisted internal fixation (SAIF) reconstructs and internally fixates the most severe osteoporotic vertebral fractures

Abstract: BackgroundThe treatment of severe osteoporotic vertebral compression fractures (VCFs) with middle-column (MC) involvement, high fragmentation, large cleft and/or pedicular fracture is challenging. Minimally invasive 'stent-screw-assisted internal fixation' (SAIF) can reduce the fracture, reconstruct the vertebral body (VB) and fix it to the posterior elements.ObjectiveTo assess feasibility, safety, technical and clinical outcome of the SAIF technique in patients with severe osteoporotic VCFs.Methods80 treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 30 publications
0
29
1
Order By: Relevance
“…Cement leakage was detected in 10% of cases on postprocedure CT, with an epidural or foraminal location in 3.8%, without clinical relevance. The authors concluded that the SAIF technique is a feasible, safe, and effective minimally invasive procedure of internal stabilization for severe osteoporotic vertebral compression fractures with middle column involvement [55]. As for SpineJack®, a pioneering comparative randomized prospective study in 300 patients with osteoporotic compression fractures type A1 of the AO Spine classification demonstrated that the group that underwent the application of SpineJack® obtained a significantly higher restoration of the vertebral body height than kyphoplasty, with both clinical and functional outcomes similar between the two techniques [19].…”
Section: Radiographic and Functional Outcomes Of Fractured Vertebral Body Reconstruction With Expandable Intravertebral Implantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cement leakage was detected in 10% of cases on postprocedure CT, with an epidural or foraminal location in 3.8%, without clinical relevance. The authors concluded that the SAIF technique is a feasible, safe, and effective minimally invasive procedure of internal stabilization for severe osteoporotic vertebral compression fractures with middle column involvement [55]. As for SpineJack®, a pioneering comparative randomized prospective study in 300 patients with osteoporotic compression fractures type A1 of the AO Spine classification demonstrated that the group that underwent the application of SpineJack® obtained a significantly higher restoration of the vertebral body height than kyphoplasty, with both clinical and functional outcomes similar between the two techniques [19].…”
Section: Radiographic and Functional Outcomes Of Fractured Vertebral Body Reconstruction With Expandable Intravertebral Implantsmentioning
confidence: 99%
“…Distefano et al applied the stent-screw-assisted internal fixation to reduce vertebral compression fractures, reconstruct the vertebral body, and fix it to the posterior elements by a technique previously described by the same group [ 49 , 55 ]. The technique rationale is that the stents obtain and maintain fracture reduction while the pedicle screws anchor the VBS-cement complex to the posterior elements, avoiding its displacement, and act as a bridge across the middle column, preserving its integrity from possible collapse and splitting [ 49 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasingly complex osteoporotic and traumatic fractures with severe kyphosis, burst morphology with middle column and posterior column (PC) involvement, and nonunions all can lead to progressive collapse. 57 In these more severe and high-risk morphologies, failure of VA can occur with distraction of fragments, resulting in severe kyphosis, development of neurologic symptoms, and the need for surgical revision.…”
Section: Future Directionsmentioning
confidence: 99%
“… 7 , 8 In recent years, a new minimally invasive technique, called Stent-Screw Assisted Internal Fixation (SAIF), was developed based on the VBS system and can be applied in severe neoplastic and osteoporotic fractures. 9 , 10 It has good clinical efficacy and biomechanical support. 11 , 12 The VBS/PMMA can effectively reconstruct the load-bearing capacity of the anterior column.…”
Section: Introductionmentioning
confidence: 99%